Diagnostic and Therapeutic Dilemmas in Inguinal Endometriosis: A Case Report - Faiza Fardha Auliya; Yudi Siswanto (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Endometriosis is a common gynecological condition, but its extragenital forms, particularly inguinal endometriosis, are rare and pose significant diagnostic and therapeutic challenges. This case highlights the complexities encountered in managing endometriosis in an unusual location. Case Presentation: We report the case of Mrs. C, a 34-year-old married woman, who presented with a 4-year history of a painful, cyclically bleeding lump in the right pubic region, was initially misdiagnosed as a traumatic cyst. Histopathological examination of an external genital biopsy in 2023 confirmed endometriosis. Initial monthly Depo Medroxyprogesterone Acetate (DMPA) therapy for six cycles proved ineffective. Subsequently, Gonadotropin-Releasing Hormone (GnRH) agonist (Endrolin) injections were administered for a total of 12 cycles, with symptom improvement, specifically cessation of bleeding, noted only after the seventh cycle. No hypoestrogenic side effects were reported despite prolonged GnRH agonist use without add-back therapy. Conclusion: This case illustrates the diagnostic delay often associated with extragenital endometriosis due to its atypical presentation, with the patient receiving only symptomatic treatment for years. The need for prolonged GnRH agonist therapy (12 cycles), exceeding standard guidelines of six months, highlights individual variability in treatment response, even without add-back therapy. Recurrence of bleeding occurred shortly after cessation of Dienogest maintenance therapy due to economic constraints, underscoring the chronic, hormone-dependent nature of the disease and the importance of continuous, accessible treatment. The patient consistently declined operative laparoscopy for wider excision.